PEMANFAATAN KONTEN INSTAGRAM SEBAGAI MEDIA PROMOSI DALAM MEMBANGUN BRAND AWARENESS PADA EVENT SOLO MARKET FEST - Caesario, Much Rizky Dela; Astuti I, Andri; Sihabuddin, Sihabuddin (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study examines the use of Instagram content as a promotional medium to build brand awwareness for the solo market fest event. In the digital era, social media has become a primary tool in marketing strategies, especially Instagram, which has a wide reach and interactive features. This research employs a qualitative method with a descriptive approach. Data was collected through interviews with Solo Market Fest social media managers, visitors, and UMKM and thrifting tenants. The findings indicate that the promotional strategies implemented through engaging visual content, interactive features such as giveaways and polls, and the use of hashtags effectively enhance brand awareness. The application of the AISAS model (Attention, Interest, Search, Action, Share) in promotional strategies helps attract attention, increase audience interest, facilitate information searches, drive action, and expand promotional reach through content sharing. Thus, Instagram proves to be an effective platform for building brand awareness at the Solo Market Fest event. Additionally, this study finds that active user engagement in digital interactions on Instagram strengthens audience loyalty to the event. Instagram not only functions as a promotional medium but also as an effective communication tool for building a community and enhancing relationships between organizers, tenants, and visitors. Therefore, optimizing digital marketing strategies through Instagram can be a key factor in the success of similar events in the future.